Higher Nrf2 Level is Correlated with Metabolic Parameters in Type 2 Diabetes Mellitus - Rina Triana; Indriyanti Rafi Sukmawati; Mas Rizky Anggun Adipurna Syamsunarno; Keri Lestari (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is the most common metabolic disorder associated with oxidative stress and chronic inflammation. Understanding the regulatory mechanisms related to the role of nuclear factor erythroid 2 (Nrf2), a master regulator of cellular antioxidant defenses, in individuals with T2DM, is essential. Therefore, in-depth investigation regarding the associations between Nrf2 levels, and metabolic parameters, such as waist circumference, fasting glucose levels, HbA1C, and serum inflammatory markers expressions is needed to elucidate the mechanisms driving T2DM and its metabolic disturbances.METHODS: This was a cross-sectional study including 90 T2DM and 25 healthy subjects. Nrf2 level; serum inflammatory markers levels, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, interferon (IFN)-α2, IFN-g, monocyte chemoattractant protein (MCP)-1, IL-10, IL-12p70, IL-17A, IL-18 and IL-23; as well as waist circumference; fasting glucose levels; and HbA1C were measured. Nrf2 concentrations in peripheral blood mononuclear cells were determined using enzyme-linked immunosorbent assay (ELISA), while serum inflammatory markers concentrations were quantified with flowcytometry.RESULTS: Nrf2, TNF-α, and IL-17A levels were significantly higher in the T2DM group, while IL-1β, IFN-α 2, IL-10, IL-12p70, and IL-23 levels were elevated in healthy controls Nrf2 exhibited positive correlations with waist circumference, fasting glucose, HbA1C, and TNF-α. Conversely, an inverse correlation of Nrf2 was observed with IL-1β, IL-12p70 and IL-17A.CONCLUSION: Correlations between Nrf2 and metabolic clinical parameters suggest its role in regulating glucose metabolism and adiposity. Elevated Nrf2 levels observed in T2DM patients may present novel therapeutic avenues for enhancing endogenous antioxidant defenses.KEYWORDS: type 2 diabetes mellitus, Nrf2, oxidative stress, inflammation, metabolic regulation, therapeutic strategies